The Role of Entrepreneurship in Achieving Sustainable Development Goals in The Light of The Kingdom’s Vision 2030: An applied study on the Asir region secretariat - Alnemi, Emtenan Hasan (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to identify the role of entrepreneurship in achieving the dimensions of sustainable development in the light of the Kingdom’s Vision 2030, an applied study in the Municipality of Asir Region, and the researcher relied on the descriptive analytical and relational approach, and the statistical program SPSS was used, and this study included a field survey of a sample of (279) individuals, and the researcher used the questionnaire as a tool to collect data in the study, and descriptive and inferential statistical methods were used to analyze the data. The results found that the total impact of entrepreneurship in the economic dimension is (33.7%), the total impact of entrepreneurship in the social dimension is (24.9%), and the total impact of entrepreneurship in the environmental dimension is (17.6%), as well as the study found a very high and high degree of approval about the reality of practicing the dimension of entrepreneurship, the economic dimension, the social dimension and the environmental dimension in the Asir region from the point of view of the research sample surveyed. Based on these results, the study recommended providing all means of support to entrepreneurs for the development and development of entrepreneurial investment projects with a positive return that contributes to achieving the goals of the Kingdom’s Vision 2030 in the field of sustainable development, encouraging entrepreneurs to innovate environmental management projects and moving towards a green economy by directing entrepreneurs to and relying on ecosystems and new environmental investments and attention to clean water and sanitation services, Activating the role of partnership for entrepreneurship and sustainable development between the government and the sector Private, civil society and citizens alike, develop plans and studies that enable the crystallization of sustainable local economic projects.